Using item response theory to describe the Nonverbal Literacy Assessment (NVLA). Issue 4 (13th February 2018) - Fleming, Danielle; Wilson, Mark; Ahlgrim‐Delzell, Lynn
Abstract: The Nonverbal Literacy Assessment (NVLA) is a literacy assessment designed for students with significant intellectual disabilities. The 218‐item test was initially examined using confirmatory factor analysis. This method showed that the test worked as expected, but the items loaded onto a single factor. This article uses item response theory to investigate the NVLA using Rasch models. First, we reduced the number of items using a unidimensional model, which resulted in high levels of test reliability despite decreasing the number of questions, providing the same information about student abilities in less time. Second, the multidimensional analysis indicated that it is possible to view the NVLA as a test with four dimensions, resulting in more detailed information about student abilities. Finally, we combined these approaches to obtain both specificity and brevity, with a four‐dimensional model using 133 items from the original NVLA.